Performance testing of reciprocating compressor / Wan Noorhayani Wan Ahmad Samsuddin and Noraini Mohamad Bayuri - Wan Ahmad Samsuddin, Wan Noorhayani; Mohamad Bayuri, Noraini (2001)
Compressor is one of the most important mechanical equipment. The function of compressor is to compress gases to a higher pressure. By virtue of this compression, the pressure density and temperature of the compressed gas will increase.